The Association Between Psychopathology Ans Quality Of Life In Burn Patients At Dr. Cipto Mangunkusumo Hospital, Jakarta - Winanda, Rizki Aniza; Kusumadewi, Irmia; Wardhana, Aditya; Wiguna, Tjhin; Raharjanti, Natalia Widiasih (Jurnal Plastik Rekonstruksi, 2017)
Background : Burns result in severe injuries that cause damage or loss of tissue due to contact with sources of heat resulting in injuries to all body systems. Injuries of the skin, which functions as a barrier to protect internal organs, may cause patients to experience damage to one's physical appearance and body image causing negative feelings that may lead to other problems such as psychopathology and symptoms of mental illness. Method : A cross sectional study with consecutive sampling method of burn patients who were treated at the Plastic Surgery Outpatient Clinic and Burn Unit of RSCM was conducted between April-May 2017. Subjects were asked to fill in self-report questionnaires including patient identity form, SRQ-20 (cutoff point ?6) for presence of psychopathology, and WHOQoL-BREF to obtain mean scores of quality of life that include four domains of physical, psychological, social, and environment assessment. Data collected was analyzed using correlation analysis. Result : 56 burn patients were included in the study. 30.4% did not work and 48.2% had very low income per month. 67.9% patients experienced burns due to fire and 44.6% had burns 10-30% of the TBSA with a majority of patients (80.4%) experiencing a combination of second & third degree burns. Based on the analysis, 57.1% of patients had a form of psychopathology and low mean scores of quality life (physical domain 48.1, psychological domain 51.5). Significant negative correlations (p ? 0.05) were obtained between the psychological domain and symptoms of depression, anxiety, low energy; physical domain and low energy; and social domain with anxiety. Conclusion: This study obtained significant results to identify the correlation between psychopathology and various domains of quality of life affected.